Hope at sea : an adventure story - Miyares, Daniel (Anne Schwartz Books, 2021)
"Hope doesn't want to listen to her father's stories about his voyages at sea. She wants to be part of those stories! Now's her chance.... She will stow away on Papa's ship. But look! the wind has picked up, and the sky is darkening. Batten down the hatches! Could there be such a thing as an adventure that is too exciting? Join high-spirited Hope on a trip of alifetime in this exquisitely illustrated picture book that also captures the love between a father and child." --